Exploring the Geography of Corporate Philanthropic Disaster Response: A Study of Fortune Global 500 Firms - Muller, Alan (Journal of business ethics, 2009)
In recent years, major disasters have figured prominently in the media. While corporate response to disasters may have raised corporate philanthropy to a new level, it remains an understudied phenomenon. This article draws on comparative research on corporate social responsibility (CSR) and corporate philanthropy to explore the geography of corporate philanthropic disaster response. The study analyzes donation announcements made by Fortune Global 500 firms from North America, Europe and Asia to look for regional patterns across three recent disasters: the South Asian Tsunami, Hurricane Katrina, and the Kashmiri earthquake. The results reveal inter-regional differences in the overall likelihood of donations and in their cash value, in addition to the identification of home-region- and local presence effects. Implications for researchers and practitioners are discussed.